Cтабілізація динамічних характеристик гідроприводу з використанням пасивних гасників пульсацій - Панченко, Анатолій Іванович; Волошина, Анжела Анатоліївна; Панченко, Ігор Анатолійович; Мітков, Василь Борисович; Волошин, Анатолій Анатолійович; Panchenko, Anatolii; Voloshina, Angela; Panchenko, Ihor; Mitkov, Vasyl; Voloshin, Anatolii (Запоріжжя : ТДАТУ, Видавничій дім "Гельветика", 2025)
UA: Статтю присвячено вирішенню важливої наукової проблеми забезпечення стабільності динамічних характеристик гідроприводу під час перехідних процесів із застосуванням пасивних гасників пульсацій. У результаті виконаних робіт удосконалено математичну модель, що дає змогу досліджувати вплив пасивного гасника пульсацій на стабілізацію вихідних характеристик гідроприводу. Установлено, що під час розгону гідроприводу амплітуда стрибків тиску і крутного моменту визначається часом відкриття (спрацьовування) запобіжного клапана. Застосування пасивного гасителя пульсацій збільшує час відкриття запобіжного клапана в сім разів, що дає змогу знизити стрибки тиску і крутного моменту в 2,2 рази. Таким чином, застосування пасивного гасника пульсацій, що працює як демпфуючий пристрій, дає змогу стабілізувати динамічні характеристики гідроприводу під час перехідних процесів. /// EN: One of the ways to ensure the stability of the output characteristics of hydraulic drives of mechatronic systems of self-propelled vehicles is the use of passive pulsation dampers, which allow smoothing out the pressure surges of the working fluid that occur during transient processes. As a result of the research, a mathematical model has been refined that describes the transient processes that occur in hydraulic drives and their elements, which includes the operation of the pump, planetary hydraulic motor and safety valve in the conditions of operation of self-propelled vehicles, when a passive pulsation damper is connected. The refined model allows us to study the influence of a passive pulsation damper on the stabilization of dynamic processes that occur in a hydraulic drive with a planetary hydraulic motor during transient processes in the conditions of operation of self-propelled vehicles. It has been established that when the hydraulic drive is accelerated, the magnitude of pressure and torque surges are determined by the opening time of the safety valve. The use of a passive pulsation damper increases the operating time (opening) of the safety valve by 7 times from 0.01 s to 0.07 s. This allows, at the moment of starting the hydraulic drive of the mechatronic system of self-propelled equipment, to reduce pressure and torque jumps by 2.2 times. In a stable operating mode, the pulsation damper stabilizes pulsations caused by fluctuations in the external disturbing load, as well as fluctuations caused by uneven pump supply. The use of a passive pulsation damper, which works as a damping device, allows stabilizing the dynamic processes occurring in hydraulic drives and their elements during transient processes, as well as in a stable operating mode during the operation of self-propelled equipment.
Stabilization of dynamic characteristics of a hydraulic drive using passive pulsation dampers
Keywords: пасивний гасник пульсацій; структурно-функціональна схема; динамічна модель; динамічні характеристики; passive pulsation damper; structural and functional diagram; dynamic model; dynamic characteristics